Managing the Gap Between Actual and Target Capital Structure: An Evidence From Pakistan - RAFAY, ABDUL; GILANI, USMAN JAVED; IJAZ, FARRUKH (Journal of Management and Research, 2014)
Investment framework is one of the most significant components that impact the company’s value. Reliable funding choices for a company generally lead to a capital structure that increases the firm’s value (Abor, 2006). Early studies provide contradictory reviews about a company’s capital structure decisions. This paper investigates the partial adjustment model for a company’s target capital structure. The study also explores how companies operating in different sectors of Pakistani market adjust towards the target capital structure levels. The study also recognizes that an unanticipated share price change also have an effect on the target capital structure. The results indicate that companies do have target leverage and that their adjustment speed varies from sector to sector of the Pakistani market. A typical sector closes more than 50% of the gap between its actual and its target debt ratios within one year.